Hydrodynamic simulation of Cygnus OB2: the absence of a cluster wind termination shock - Vieu, Thibault; Larkin, Cormac; Härer, L.; Reville, Brian; Sander, Andreas A. C.; Ramachandran, Varsha (Monthly notices of the Royal Astronomical Society, 2024)
ABSTRACT -We perform a large-scale hydrodynamic simulation of a massive star cluster whose stellar population mimics that of the Cygnus OB2 association. The main-sequence stars are first simulated during 1.6 Myr, until a quasi-stationary state is reached. At this time, the three Wolf-Rayet stars observed in Cygnus OB2 are added to the simulation, which continues to 2 Myr. Using a high-resolution grid in the centre of the domain, we can resolve the most massive stars individually, which allows us to probe the kinetic structures at small (parsec) scales. We find that, although the cluster excavates a spherical ‘superbubble’ cavity, the stellar population is too loosely distributed to blow a large-scale cluster wind termination shock, and that collective effects from wind-wind interactions are much less efficient than usually assumed. This challenges our understanding of the ultra-high energy emission observed from the region.